Biodiversity and application prospects of fungal endophytes in the agarwood-producing genera, Aquilaria and Gyrinops (Thymelaeaceae): A review - Li, Tianxiao; Qiu, Zidong; Lee, Shiou Yih; Li, Xiang; Gao, Jiaqi; Jiang, Chao; Huang, Luqi; Liu, Juan (Elsevier Ltd., 2023)
Agarwood is originated from the resinous part of Aquilaria and Gyrinops plants and has been a precious biomaterial for applications in traditional medicine, perfumery, cosmetics, and religious purposes all over the world. In the wild, the formation of agarwood is related to the defense mechanism of the tree in response to physical damage that allows further microbial infestation into its wood, while having the whole tree covered with agarwood would take up a long time, and it rarely happens. For Aquilaria and Gyrinops, the presence of endophytes is mainly found derived from the tree. The isolated endophytes could be important sources of natural products, while some could contribute to the formation of agarwood in the tree, which is safe for the environment and human health. This review summarized the biodiversity of fungal endophytes recorded in Aquilaria and Gyrinops and their potential effects on host trees. Till now, 67 endophytic genera have been isolated from Aquilaria and Gyrinops, and 18 ones were found responsible for the promotion of agarwood formation. Additionally, 92 compounds have been reported to be produced by the agarwood endophytes, and 52 ones displayed biological activities, most of which have anti-inflammatory, anti-bacterial, and anti-cancer activities. Nevertheless, fungal endophytes are promising agents that deserved to be further studied and scaled up to a commercial level for the production of agarwood oil, but the role of endophytes in the agarwood host trees needs to be furtherly investigated in future studies.